Reforma trabalhista e inconstitucionalidade na efetivação da tutela laboral: impactos processuais da lei n° 13.467/17 no acesso à justiça dos trabalhadores - Dias, Crizeuda Farias da Silva (2021)
The 1988 Constitution of the Federative Republic of Brazil – CRFB/1988 – guaranteed the protection of workers' rights. However, in 2017, such legislation, which remained fundamentally based on the principle of worker protection and the promotion of the criterion of social justice, was modified by Law Nº 13.467/17, which brought a new configuration to procedural gratuitousness in the Court of Work, differentiating the requirements for the granting of free legal aid, which in the Labor Court became more burdensome than those of the Civil Procedure and, therefore, disrespect the constitutional principle of equality and hinder access to the Labor Court, contrary to a fundamental precept. Thus, it is questioned to what extent these procedural innovations compromise workers’access to justice. In light of this main problem, in evaluating the new labor normative sphere, it is necessary to evaluate: how does this phenomenon materialize in practice? In the legal perspective, the reflection starts from a hermeneutic analysis that guides the constitutional non-conformation of the precepts inserted in the CLT text, which affront the constitutional principle of equality and the right of access to justice. The objective is to determine whether such measures at first, are the cause of the decrease in the number of labor claims. In this sense, in this dissertation, the constitutional parameters for the valuation of work, the social value of work in the CRFB/1988 and the importance of social rights are addressed. More specifically, the importance of work as a guaranteeing instrument of human dignity is addressed, enabling the precepts of article 170, items VII and VIII, of the CRFB/1988 and its normative repercussions on fundamental procedural labor rights. It discusses the concepts of Democratic state and economic development linked to the right of access to justice. It discusses the right of access to justice in the Universal Declaration of Human Rights as a promoter of socio-labor rights, examining the relevance of the principle of protection to the under-sufficient in the procedural legal relationship of the Labor Claim, the institute of jus postulandi, its relevance in labor legislation for access to justice for workers and employers and the principle of free justice. Furthermore, a critical analysis of the new labor procedural provisions is made: procedural costs, attorney and expert fees in view of the principle of prohibition of social retrogression, investigating the material validity of these provisions from the perspective of the principle of progressivity. In addition, in order to correlate legislative changes with reality, a comparative analysis of the statistical data provided by the Coordination of Statistics and Research of the TST is carried out, in order to confirm that the number of actions filed in the knowledge phase has been decreased throughout the national territory, proving that the Reform, by imposing procedural burdens on workers to claim their rights, achieved its objective of push them away from the Labor Court, preventing the full implementation of the principle of access to justice for Brazilian workers.